N-Substituted 2-(Benzenosulfonyl)-1-Carbotioamide Derivatives Exert Antimicrobial and Cytotoxic Effects via Aldehyde Dehydrogenase Pathway: Synthesis, In Silico and In Vitro Studies - Lucja Walczak-Nowicka; Anna Biernasiuk; Wojciech Ziemichód; Zbigniew Karczmarzyk; Mateusz Kwaśnik; Paweł Kozyra; Waldemar Wysocki; Agnieszka Stenzel-Bembenek; Dorota Kowalczuk; Mariola Herbet; Monika Pitucha (MDPI AG, 2023)
A series of N-Substituted 2-(benzenosulfonyl)-1-carbotioamide derivatives (WZ1-WZ4) were synthesized and characterized using spectral methods. A comprehensive activity study was performed for each compound. All compounds were tested for antibacterial activity. Moreover, in silico studies were carried out to determine the anticancer potential of the designed WZ1-WZ4 ligands. Based on molecular docking, aldehyde dehydrogenase was selected as a molecular target. The obtained data were compared with experimental data in vitro tests. Novel hybrids of the thiosemicarbazide scaffold and sulfonyl groups may have promising anticancer activity via the aldehyde dehydrogenase pathway. The best candidate for further studies appears to be WZ2, due to its superior selectivity in comparison to the other tested compounds.